Studies on the Mechanism of Interference by Fibrinogen Degradation Products (FDP) with the Platelet Function Role of Fibrinogen in the Platelet Atmosphere - Maria, Kopeć; Budzyński, A; Stachurska, Jolanta; Węgrzynowicz, Z; Kowalski, E (Thrombosis and Haemostasis, 1966)
1. Blood platelets can be aggregated by solutions of fibrinogen preparations of different origins. Fibrinogen degradation products (FDP) obtained by plasmin digestion do not aggregate platelets.2. Preparations of FDP added to platelet suspension inhibit aggregation induced by fibrinogen,.3. FDP when added to platelet suspensions, inhibit the release of adenine nucleotides induced by thrombin, connective tissue extract, kaolin or the contact factor.4. Platelet suspensions pretreated with SKPL loose partly the ability to release adenine nucleotides after the action of inducing agents.5. Washed platelet suspensions possess the capacity to adsorb fibrinogen and FDP, the latter being adsorbed in greater amounts and bound stronger than fibrinogen.6. An attempt was undertaken to explain the observed phenomena on the basis of a general view on the molecular mechanism of platelet function.It is postulated that fibrinogen is an integral part of the platelet surface and that it is one of the determinants of the platelet surface properties. Fibrinogen is necessary for platelet aggregation by ADP and for the adequate action of the agents which initiate metabolic changes and induce the release reaction. FDP act antagonistically to fibrinogen. They inhibit ADP aggregation as well as the access to the susceptible sites on. the surface of the platelet of the agents inducing release.